THE INFLUENCE OF GRDP PER CAPITA, PMTB, EMPLOYMENT STATUS AND INCOME DISTRIBUTION ON COMMUNITY WELFARE IN DISTRICTS/CITIES OF BALI PROVINCE - Ni Luh Gede Ayu Sri Mahayoni; I Gusti Wayan Murjana Yasa (Adisam Publisher, 2025)
The aim of this research is to analyze GRDP per capita, PMTB, employment status, and income distribution on community welfare in the District/City of Bali Province. This research uses secondary data with a quantitative approach, this research uses 72 data. Data analysis techniques use descriptive statistical analysis and multiple linear regression analysis. The results of this research show 1) GRDP per capita, PMTB, Employment Status, and Income Distribution simultaneously have a positive and significant effect on Community Welfare in the Regency/City of Bali Province, 2) GRDP Per Capita, PMTB, and Employment Status partially have a positive and significant effect on Community Welfare in the Regency/City of Bali Province, 3) Income Distribution partially has a negative and insignificant effect on Community Welfare in the Regency/City of Bali Province. The results of this research are expected to be able to provide an overview that can be used as consideration for the government so that the resulting policy is able to provide positive impact on the community in the Regency/City of Bali Province.